Strategi Pemasaran Perusahaan Logistik - Diah Ayu Wulandari; Aswanti Setyawati (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
The purpose of the study was to assess the effect of marketing strategy of the company’s performance and the role of competition environment in moderating the marketing strategy of the company’s performance. The MRA (Moderated Regression Analysis) was used as the analyzing method. The result shows that there is a significant and positive effect of the marketing strategy of the company’s performance (r = 0, 912), and a significant and positive effect of the logistics competition environment of the company’s performance (r = 0, 955). The role of competition environment in moderating the negative relation between marketing strategy and company’s performance since the competition environment comes from outside and could threaten the company’s marketing and decrease the performance.